Identifikasi faktor resiko utama pada kanker paru non-smoker - Effendy, Lyndia; Pribadi, Florence; Kusumah, Irwin Priyatna; Manurung, Riska Enjelica (Holistik Jurnal Kesehatan, 2025)
Background: Lung cancer in non-smokers represents a distinct clinical and biological entity from smoking-associated lung cancer, characterized by different risk factors, molecular profiles, and prognosis. Understanding the predominant risk factors in this population is critical for early detection, prevention, and personalized treatment. Purpose: To identify and elucidate the most common risk factor for lung cancer in non-smokers through an integrative review of epidemiological, genetic, and environmental research, highlighting their clinical relevance. Method: The literature review and article search were conducted using the PCC framework (Population, Concept, Context) with sources extracted from three databases: Google Scholar, PubMed, and Scopus. The keywords used included "psychological stress" AND "lung cancer" AND "non-smoker". Inclusion criteria for articles were as follows: published between 2000–2025, full-text available, open-access, published in scientific journals, written in English or Indonesian, original research studies. Results: Among the identified risk factors secondhand smoke exposure, genetic predispositions, environmental pollutants, oncogenic viruses, and pre-existing lung diseases exposure to secondhand smoke (environmental tobacco smoke) emerges as the most common and well-supported risk factor for lung cancer in non-smokers. Meta-analyses report a 15-27% increased risk associated with spousal or occupational exposure, underscoring its epidemiological significance. Genetic mutations such as EGFR and ALK rearrangements are prevalent in non-smoker lung cancer patients but represent somatic changes rather than primary risk factors. Other contributors like radon exposure, cooking fumes (particularly in developing countries), and infections have variable and less consistent evidence. Screening guidelines currently do not extend to non-smokers due to insufficient risk stratification. Conclusion: The predominant risk factor for lung cancer in non-smokers is exposure to secondhand tobacco smoke. This highlights the critical public health need to reduce environmental tobacco exposure. Suggestion: Further research is needed to clarify the pathogenic contribution of other factors and to develop tailored screening criteria for non-smoking populations.   Keywords: Lung Cancer; Non-Smoker; Risk Factors Identification.   Pendahuluan: Kanker paru pada non-perokok merupakan entitas klinis dan biologis yang berbeda dari kanker paru terkait merokok, ditandai dengan faktor risiko, profil molekuler, dan prognosis yang berbeda. Memahami faktor risiko utama pada populasi ini sangat penting untuk deteksi dini, pencegahan, dan pengobatan yang dipersonalisasi. Tujuan: Untuk mengidentifikasi dan menjelaskan faktor risiko paling umum untuk kanker paru pada non-perokok melalui tinjauan integratif penelitian epidemiologi, genetik, dan lingkungan, dengan menekankan relevansi klinisnya. Metode: Penelitian review literature sistemik dilakukan dengan kerangka PCC (Population, Concept, Context) menggunakan sumber literature yang diambil dari tiga basis data: Google Scholar, PubMed, Scopus. Kata kunci yang digunakan meliputi sudi hubungan AND stress AND kanker paru AND non-smoker. Kriteria inklusi artikel antara lain artikel yang dipublikasi tahun 2000-2025, full text, akses terbuka, jurnal ilmiah, ditulis dalam Bahasa Inggris dan Indonesia serta penelitian asli. Hasil: Diantara faktor risiko yang teridentifikasi - paparan asap rokok orang lain (secondhand smoke), predisposisi genetik, polutan lingkungan, virus onkogenik, dan penyakit paru yang sudah ada sebelumnya, paparan asap rokok orang lain (environmental tobacco smoke) muncul sebagai faktor risiko yang paling umum dan didukung bukti kuat untuk kanker paru pada non-perokok. Meta-analisis melaporkan peningkatan risiko sebesar 15-27% terkait paparan dari pasangan atau lingkungan kerja, yang menegaskan signifikansi epidemiologisnya. Mutasi genetik seperti penyusunan ulang EGFR dan ALK memang prevalen pada pasien kanker paru non-perokok, tetapi lebih merupakan perubahan somatik daripada faktor risiko primer. Kontributor lain seperti paparan radon, asap memasak (terutama di negara berkembang), dan infeksi memiliki bukti yang bervariasi dan kurang konsisten. Pedoman skrining saat ini belum mencakup non-perokok karena stratifikasi risiko yang belum memadai. Simpulan: Faktor risiko utama kanker paru pada non-perokok adalah paparan asap rokok orang lain. Hal ini menyoroti kebutuhan mendesak dalam kesehatan masyarakat untuk mengurangi paparan tembakau di lingkungan. Saran: Penelitian lebih lanjut diperlukan untuk memperjelas kontribusi patogenik dari faktor-faktor lain dan mengembangkan kriteria skrining yang disesuaikan untuk populasi non-perokok.   Kata Kunci: Faktor Resiko Utama; Kanker Paru; Non-Smoker.